Long Non-Coding RNAs Regulating Macrophage Functions in Homeostasis and Disease - Scacalossi, Kaitlyn R. (Vascul Pharmacol, 2018)
Non-coding RNAs, once considered “genomic junk”, are now known to play central roles in the dynamic control of transcriptional and post-transcriptional gene expression. Long non-coding RNAs (lncRNAs) are an expansive class of transcripts broadly described as greater than 200 nucleotides in length. While most lncRNAs are species-specific, their lack of conservation does not imbue a lack of function. LncRNAs have been found to regulate numerous diverse biological functions, including those central to macrophage differentiation and activation. Through their ability to form RNA-DNA, RNA-protein and RNA-RNA interactions, lncRNAs have been implicated in the regulation of myeloid lineage determination, and innate and adaptive immune functions, among others. In this review, we discuss recent advances, current challenges and future opportunities in understanding the roles of lncRNAs in macrophage functions in homeostasis and disease.